The Effect of Triglycerides and Total Cholesterol Levels of Lipemic Plasma on The Results of HBsAg Screening Using Chemiluminescence Immunoassay - Ranti Dwi Astriani; Ni Ken Ritchie; Mohamad Sadikin (JURNAL INFO KESEHATAN, 2025)
The results of the Immunochromatographic Method for Infectious Disease Testing (IMLTD) may vary depending on the presence of lipids in donor blood samples, potentially leading to false‐negative or false‐positive outcomes in hepatitis B surface antigen (HBsAg) screening. This study aimed to evaluate the effect of lipid interference on HBsAg screening using the chemiluminescent immunoassay (CLIA) method, to determine the range of triglyceride levels that may influence test results (100 mg/dL to >3000 mg/dL), and to assess practical lipid removal methods to ensure blood safety. An experimental laboratory study was conducted using two sample groups. The first group consisted of six bags of non-lipemic, HBsAg-reactive plasma that were rendered lipemic by the addition of Lipofundin. The second group included 25 bags of lipemic donor plasma that were non-reactive in the initial IMLTD screening and subsequently subjected to lipid removal treatments. Lipid reduction was performed using centrifugation, polyethylene glycol (PEG), and diethyl ether. The results showed no significant differences in HBsAg values before and after Lipofundin addition, indicating that lipemia did not affect HBsAg detection by the CLIA method. However, lipid removal using centrifugation, PEG, and diethyl ether significantly reduced triglyceride and total cholesterol levels (p < 0.05) in lipemic samples that interfered with CLIA analysis. In conclusion, lipemia does not directly affect HBsAg screening results using the CLIA method; however, lipid removal procedures are effective and necessary for managing highly lipemic samples to maintain the accuracy and reliability of blood screening tests.